Trailing Nocardiosis- A Non-healing Wound Infection: Where does Bangladesh stand? An Updated Review! - Hasan, Sadah; Delwar, Umama Binte; Dilshad, Khadiza; Anwar, Kazi Selim; Lutfor, Afzalunnessa Binte (The Journal of Ad-din Women’s Medical College, 2023)
Abstract not available The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 42-47